NOBCChE Newsletter, Volume 5, Number 2 (National Organization for Black Chemists and Chemical Engineers, 1984)
March 1984 issue of the National Organization for the Professional Advancement of Black Chemists and Chemical Engineers (NOBCChE) Newsletter.
Keywords: National Organization for Black Chemists and Chemical Engineers; Newsletters; African American chemists; African American engineers; Chemical engineers; Chemists; Periodicals; Scientists, Black; African American scientists